Photosynthetic Light Responses May Explain Vertical Distribution of Hymenophyllaceae Species in a Temperate Rainforest of Southern Chile. - María José Parra; Karina I Acuña; Angela Sierra-Almeida; Camila Sanfuentes; Alfredo Saldaña; Luis J Corcuera; León A Bravo (PLoS ONE)
Some epiphytic Hymenophyllaceae are restricted to lower parts of the host (< 60 cm; 10-100 μmol photons m(-2) s(-1)) in a secondary forest of Southern Chile; other species occupy the whole host height (≥ 10 m; max PPFD > 1000 μmol photons m(-2) s(-1)). Our aim was to study the photosynthetic light responses of two Hymenophyllaceae species in relation to their contrasting distribution. We determined light tolerance of Hymenoglossum cruentum and Hymenophyllum dentatum by measuring gas exchange, PSI and PSII light energy partitioning, NPQ components, and pigment contents. H. dentatum showed lower maximum photosynthesis rates (A max) than H. cruentum, but the former species kept its net rates (An) near Amax across a wide light range. In contrast, in the latter one, An declined at PPFDs > 60 μmol photons m(-2) s(-1). H. cruentum, the shadiest plant, showed higher chlorophyll contents than H. dentatum. Differences in energy partitioning at PSI and PSII were consistent with gas exchange results. H. dentatum exhibited a higher light compensation point of the partitioning of absorbed energy between photochemical Y(PSII) and non-photochemical Y(NPQ) processes. Hence, both species allocated energy mainly toward photochemistry instead of heat dissipation at their light saturation points. Above saturation, H. cruentum had higher heat dissipation than H. dentatum. PSI yield (YPSI) remained higher in H. dentatum than H. cruentum in a wider light range. In both species, the main cause of heat dissipation at PSI was a donor side limitation. An early dynamic photo-inhibition of PSII may have caused an over reduction of the Qa+ pool decreasing the efficiency of electron donation to PSI. In H. dentatum, a slight increase in heat dissipation due to acceptor side limitation of PSI was observed above 300 μmol photons m(-2)s(-1). Differences in photosynthetic responses to light suggest that light tolerance and species plasticity could explain their contrasting vertical distribution.